2021
DOI: 10.3389/fphys.2021.748249
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Transcarbamylase – From Structure to Metabolism: An Update

Abstract: Ornithine transcarbamylase (OTC; EC 2.1.3.3) is a ubiquitous enzyme found in almost all organisms, including vertebrates, microorganisms, and plants. Anabolic, mostly trimeric OTCs catalyze the production of L-citrulline from L-ornithine which is a part of the urea cycle. In eukaryotes, such OTC localizes to the mitochondrial matrix, partially bound to the mitochondrial inner membrane and part of channeling multi-enzyme assemblies. In mammals, mainly two organs express OTC: the liver, where it is an integral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 118 publications
4
22
0
Order By: Relevance
“…The region between residues 265 and 280 contains the conserved SMG loop, which may undergo a conformational change upon the binding of carbamoyl phosphate and ornithine that shields the active site of the enzyme. 34 It has been suggested that despite its conservation, most amino acid changes in the loop would not necessarily affect its function 35 and our results are consistent with this hypothesis.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The region between residues 265 and 280 contains the conserved SMG loop, which may undergo a conformational change upon the binding of carbamoyl phosphate and ornithine that shields the active site of the enzyme. 34 It has been suggested that despite its conservation, most amino acid changes in the loop would not necessarily affect its function 35 and our results are consistent with this hypothesis.…”
Section: Resultssupporting
confidence: 90%
“…The region between residues 265 and 280 contains the conserved SMG loop, which may undergo a conformational change upon the binding of carbamoyl phosphate and ornithine that shields the active site of the enzyme. 34 It has been suggested that despite its conservation, most amino acid changes in the loop would not necessarily affect its function 35 and our results are consistent with this hypothesis. While OTC shows a general intolerance to amino acid substitutions, we expected that altering the amino acid at an active site of the enzyme would have a particularly high likelihood of impairing OTC function and therefore inhibiting growth in our assay.…”
Section: A High Proportion Of Amino Acid Substitutions Impair Otc Act...supporting
confidence: 90%
“…Interestingly, the expression of amino acid synthesis-related genes was significantly increased. These genes include glutamine synthesis-related gs (Eelen et al, 2018), cystathionine synthesis-related csb (Casique et al, 2013), proline synthesis-related aldh18a1 (Baumgartner et al, 2000), S-adenosylmethionine synthesis-related mata2 and L-citrulline-synthesis-related oct (Couchet et al, 2021). As a consequence, the increased amino acid synthesis and decreased amino acid catabolism in the SL12 group could be attributed to the increased whole-body protein and amino acid contents in larvae.…”
Section: Sl-enriched Diets Decreased Amino Acid Catabolismmentioning
confidence: 99%
“…l ‐citrulline (CIT) is a nonessential amino acid synthesized in enterocytes from dietary l ‐arginine (ARG) and l ‐glutamine (GLN) using the ornithine carbamoyltransferase (OCT) enzyme 1 . CIT gets released into the portal vein and, as it is not taken up by the liver, reaches systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…L-citrulline (CIT) is a nonessential amino acid synthesized in enterocytes from dietary L-arginine (ARG) and Lglutamine (GLN) using the ornithine carbamoyltransferase (OCT) enzyme. 1 CIT gets released into the portal vein and, as it is not taken up by the liver, reaches systemic circulation. Circulating CIT is then taken up by the kidneys and converted into ARG by argininosuccinate synthase and argininosuccinate lyase (Figure 1).…”
Section: Introductionmentioning
confidence: 99%